Bacterial Nanocellulose—A Biobased Polymer for Active and Intelligent Food Packaging Applications: Recent Advances and Developments - Karolina Ludwicka (Polymers, 2020)
The aim of this review is to provide an overview of recent findings related to bacterial cellulose application in bio-packaging industry. This constantly growing sector fulfils a major role by the maintenance of product safety and quality, protection against environmental impacts that affect the shelf life. Conventional petroleum-based plastic packaging are still rarely recyclable and have a number of harmful environmental effects. Herein, we discuss the most recent studies on potential good alternative to plastic packaging—bacterial nanocellulose (BNC), known as an ecological, safe, biodegradable, and chemically pure biopolymer. The limitations of this bio-based packaging material, including relatively poor mechanical properties or lack of antimicrobial and antioxidant activity, can be successfully overcome by its modification with a wide variety of bioactive and reinforcing compounds. BNC active and intelligent food packaging offer a new and innovative approach to extend the shelf life and maintain, improve, or monitor product quality and safety. Incorporation of different agents BNC matrices allows to obtain e.g., antioxidant-releasing films, moisture absorbers, antimicrobial membranes or pH, freshness and damage indicators, humidity, and other biosensors. However, further development and implementation of this kind of bio-packaging will highly depend on the final performance and cost-effectiveness for the industry and consumers.